The Efficacy of CHSE Certification within Sustainable Tourism in Post-Pandemic: Facts from Indonesia - Nurul Badriyah; Mahameru Rosy Rochmatullah; Rahmawati Rahmawati; Endang Dwi Amperawati; Titin Titin (Universitas Pasundan, 2023)
By observing the recovery process of the tourism industry in Indonesia after COVID- 19, this study explores the relationship between cleanliness, health, safety, and environmental sustainability (CHSE) training on workforce competency, service quality, and tourist satisfaction. This training is a prerequisite for obtaining a CHSE certificate, recognizing best practices in four fields. This study employed a sample size of 345 respondents and utilized partial least squares-path modelling to conduct path analysis. The analysis process was carried out in several stages: testing direct relationships, two-segment and three-segment mediation relationships, and additional analysis by classifying observations based on industry type. CHSE certification significantly impacts the development of green tourist attractions, improving the image of the tourist attraction industry on social media and increasing tourist visits. This study also guides countries struggling to revive their tourism industries following the COVID-19 outbreak. This study focuses on observations of CHSE certification, which is a comprehensive guarantee of best practices covering the areas of cleanliness, health, safety, and environmental sustainability.